Technology in the Classroom: What are we looking for ? - Ramanujam, R. (Voices of Teachers and Teacher Educators, 2018)
This paper presents a critical account of the role of ICTs in meeting the need of universalization of quality education in India. It also emphasises the potentials of technology interventions in classrooms.